1974
DOI: 10.1063/1.1681110
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of vibrational relaxation in the HF, DF, HF–CO2, and DF–CO2 systems

Abstract: The laser excited fluorescence method has been employed to determine rate constants for V -+ V, R and V -+ R, T relaxation HF(v = I) and DF(v = I) by CO 2 over the temperature range from 295 to 670°K. The self-deactivation rates for HF(v = I) and DF(v = I) by ground state molecules and the rate of V -+ V, R transfer from HF(~' = I) and DF(v = I) to the CO 2 (00 0 I) state exhibit a marked decrease with increasing temperature. The results provide additional evidence for the conversion of the large vibrational e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For example, scattering probabilities for energy transfer between CO 2 (00 0 1) and N 2 ( v = 1) are characterized by an inverse temperature dependence in which the excitation probability increases as the temperature decreases, a clear signature of long-range attractive-force energy-transfer processes. This behavior has been observed experimentally for a variety of systems in addition to CO 2 /N 2 , such as the deactivation of hydrogen halides with different bath molecules. …”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, scattering probabilities for energy transfer between CO 2 (00 0 1) and N 2 ( v = 1) are characterized by an inverse temperature dependence in which the excitation probability increases as the temperature decreases, a clear signature of long-range attractive-force energy-transfer processes. This behavior has been observed experimentally for a variety of systems in addition to CO 2 /N 2 , such as the deactivation of hydrogen halides with different bath molecules. …”
Section: Introductionmentioning
confidence: 57%
“…This behavior has been observed experimentally for a variety of systems in addition to CO 2 /N 2 , such as the deactivation of hydrogen halides with different bath molecules. [20][21][22] The Sharma-Brau long-range, V-V energy-transfer model has also been applied successfully to the probability of scattering into the low rotational states (J ) 0-40) of the antisymmetric (00 0 1) stretch level of CO 2 after collisions with highly vibrationally excited pyrazine. 6 In contrast to this near-resonant energy-transfer process that characterizes the excitation of the low rotational states of CO 2 (00 0 1) by hot pyrazine, evidence for a slightly more repulsive-force energy-transfer mechanism was also observed for scattering into the higher rotational states (J > 41) of the CO 2 00 0 1 vibrational state.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational energy transfer between HF and CO 2 in full collisions has been studied in great detail [46][47][48][49][50][51][52][53][54] and it is instructive to compare these with the results of the present study. We begin by noting that numerous studies have shown that HF (vϭ1) relaxes collisionally with CO 2 via the V -V process discussed above, namely by coupling to the CO 2 (00 0 1) asymmetric stretching vibrational state.…”
Section: Comparison With Full Collision Experimentsmentioning
confidence: 99%